Synthesis of New γ-Lactam Derived from 3-Chlorobenzo [b] Thiophene and Evaluation of Anti Bacterial Activity - Zainab B Hashim (Journal of Global Pharma Technology, 2018)
New hetero cyclic, compounds derived from cinnamic acid was synthesized. 3-Chlorobenzo[b]thiophene-2-carbonyl (Z1) was synthesized from cinnamic acid and thionyl chloride . Carbohydrazide (Z2) was obtained by the reaction of 3-Chlorobenzo [b]thiophene-2-carbonyl chloride (Z1) with hydrazine hydrate. treatment of (Z1)with ethylene di amine to give (Z3) .(Z2,Z3) undergo condensation reaction with different aromatic aldehyde in absolute ethanol gave the Schiff′s bases (Z4-Z19) new γ- lactams (Z20- Z35) derivatives have been synthesized by reacting of succinic anhydride with Schiff’s bases These compounds were evaluated of the anti- bacterial activitiesKeyword: benzo[b]thiophene, γ- lactams, Schiff′s bases.